A Comprehensive Bibliometric Analysis of Brucellosis Research: Insights from CNKI and Web of Science Databases (2014-2023) - Wang J; Cao Q; Guo S; Li Y; Li G; Yan C; Zheng M; Wang D; Xi X (Journal of Multidisciplinary Healthcare, 2025)
Jin Wang,1,2,* Qing Cao,3,* Shijun Guo,1,2 Yonglin Li,1,2 Guowei Li,1,2 Chunjiang Yan,1,2 Minan Zheng,1,2 Dawei Wang,4 Xiaotu Xi1,2 1Emergency Department, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine(Guangdong Provincial Hospital of Chinese Medicine), Guangzhou, Guangdong, People’s Republic of China; 2The Second Clinical College of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People’s Republic of China; 3The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of China; 4The First Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dawei Wang, The First Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, Guangdong, People’s Republic of China, Tel +8613580469953, Email david@gzucm.edu.cn Xiaotu Xi, Emergency Department, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine(Guangdong Provincial Hospital of Chinese Medicine), Guangzhou, Guangdong, People’s Republic of China, Tel +8613929556092, Fax +86-020-81887233, Email xxttm@gzucm.edu.cnPurpose: This study aimed to analyze the current status, research hotspots, and frontiers of brucellosis from 2014 to 2023 using data from China National Knowledge Infrastructure (CNKI) and Web of Science (WoS) via CiteSpace, and to provide new insights for researchers in the field.Material and Methods: Articles related to brucellosis published from 2014 to 2023 were retrieved from CNKI and WoS databases. CiteSpace V.6.3.R3 was employed to generate network maps and perform bibliometric analysis.Results: A total of 467 references from CNKI and 3686 references from WoS were analyzed. In CNKI, the annual publication trend showed a decline, with Xu Liqing, Ma Li, and Yang Xuxin being the most prolific authors, and the Chinese Center for Disease Control and Prevention being the leading institution. The keyword cluster analysis identified 13 main clusters, while the keyword emergence map highlighted 15 keywords with the strongest emergence intensity. In contrast, WoS displayed an increasing trend in annual publications, with Heinrich Neubauer, Egyptian Knowledge Bank (EKB), and China as the top contributors in terms of authors, institutions, and countries, respectively. “Infection” was the most frequently occurring keyword. WoS analysis revealed 16 primary clusters and 25 keywords with high emergence intensity.Conclusion: Between 2014 and 2023, CNKI saw a slight dip in brucellosis studies, while WoS research on it gained growing attention. CNKI literature primarily focuses on epidemiology, clinical manifestations, complications, and diagnostic methods, while WoS literature emphasizes pathogenesis and public health management. Effective prevention and control of brucellosis require interdisciplinary, cross-sectoral, and transnational cooperation.Keywords: brucellosis, bibliometric analysis, CiteSpace, zoonotic infectious disease, One Health